1994
DOI: 10.1063/1.466977
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational spectra of penta-atomic silicon–carbon clusters. II. Linear Si2C3

Abstract: Fourier transform infrared matrix measurements carried out in conjunction with ab initio calculations reported in a companion paper by Rittby have resulted in the first identification of two fundamental vibrations, the C=C stretching mode ν3(σu)=1955.2 cm−1, and the Si–C stretching mode ν4(σu)=898.9 cm−1, of the SiC3Si cluster formed by trapping the products of the vaporization of silicon/carbon mixtures in Ar at 10 K. The observed frequencies, relative intensities, and 13C, 29Si, and 30Si isotopic shifts for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…10 In Fourier transform infrared ͑FTIR͒ matrix studies in solid argon conducted in this laboratory the 1 ͑ ϩ ͒ϭ2080.1 cm Ϫ1 band of linear SiC 4 has been identified 9 as well as the 3 ͑ u ͒ϭ1955.2 and 4 ͑ u ͒ϭ898.9 cm Ϫ1 fundamentals of linear Si 2 C 3 . 8 In both cases the excellent agreement of measured frequencies, intensities, and isotopic shifts with the results of previously published ab initio calculations for SiC 4 , 11 and new calculations 7 carried out in conjunction with the experimental work for Si 2 C 3 , were crucial to the identification of the vibrational fundamentals. Recently the matrix results guided searches in the gas phase by Saykally and co-workers which resulted in high precision measurements using infrared diode laser spectroscopy of 1 ϭ2095.458 06 cm Ϫ1 for SiC 4 ͑Ref.…”
Section: Introductionsupporting
confidence: 62%
“…10 In Fourier transform infrared ͑FTIR͒ matrix studies in solid argon conducted in this laboratory the 1 ͑ ϩ ͒ϭ2080.1 cm Ϫ1 band of linear SiC 4 has been identified 9 as well as the 3 ͑ u ͒ϭ1955.2 and 4 ͑ u ͒ϭ898.9 cm Ϫ1 fundamentals of linear Si 2 C 3 . 8 In both cases the excellent agreement of measured frequencies, intensities, and isotopic shifts with the results of previously published ab initio calculations for SiC 4 , 11 and new calculations 7 carried out in conjunction with the experimental work for Si 2 C 3 , were crucial to the identification of the vibrational fundamentals. Recently the matrix results guided searches in the gas phase by Saykally and co-workers which resulted in high precision measurements using infrared diode laser spectroscopy of 1 ϭ2095.458 06 cm Ϫ1 for SiC 4 ͑Ref.…”
Section: Introductionsupporting
confidence: 62%
“…Experimental studies are mainly carried out by optical absorption spectroscopy, 4-13 mass spectrometry ͑MS͒, 14,15 and photoelectron spectroscopy. 16,17 From Fourier-transform infrared ͑FTIR͒ studies, a series of small SiC clusters with the following geometries have been identified: triangular SiC 2 , 7,11 rhomboidal Si 3 C, 9 rhombic Si 2 C 2 , 5 linear SiC 4 , 13 linear Si 2 C 3 , 8 pentagonal Si 3 C 2 , 10 and linear Si 2 C 4 . 6 The visible absorption spectrum 11,12 of SiC 2 shows a strong absorption peak at ϳ490 nm.…”
Section: Introductionmentioning
confidence: 99%
“…An excellent overview of the structure and bonding in mixed silicon carbon clusters up to eight atoms is given by Hunsicker and Jones [4]. In addition, Rittby, Graham, and Presilla-Marquez performed combined experimental [18][19][20] and theoretical [10,11] studies. Their extensive work led to the experimental detection of many small silicon-carbon clusters.…”
Section: Introductionmentioning
confidence: 98%